Cognitive functions and neurotropic factors associated with aging: A review - Budni, Josiane (Horyzonty Wychowania, 2018)
RESEARCH OBJECTIVE: The aim of the present article was to make a narrative review about the relation of cognitive functions and neurotrophic factors with aging.THE RESEARCH PROBLEM AND METHODS: The research problem concerns the issue of aging and the changes in cognitive and biochemical functioning that may occur in this process. The article uses the method of critical analyzes as well as the analyzes of the reference literature.THE PROCESS OF ARGUMENTATION: The first section of the article discusses population aging, the second addresses changes related to cognitive functions during aging. The third part show biochemical aspects that can directly influence the cognitive functions already mentioned, and on aging in general.RESEARCH RESULTS: The result of this review points out that the world population is aging in an accelerated way and during this process of aging there are several changes in the organism of the elderly, among which stand out the cognitive and biochemical, one being directly related to the other. In this case, there is a relation of the neurotrophic factors, which may be responsible for the changes in cognitive functions, specifically spatial memory alterations.CONCLUSIONS, INNOVATIONS AND RECOMMENDATIONS: It is necessary that more studies be carried out with this population, which may trace the elderly with cognitive impairment that may be suggestive or conclusive of a neurodegenerative disease. In addition, biochemical data may contribute to the search for new therapeutic models or early identification for Alzheimer’s disease or other associated dementias.